Composites of MnO2 nanocrystals and partially graphitized hierarchically porous carbon spheres with improved rate capability for high-performance supercapacitors. (November 2015) - Wang, Xiaolei; Fan, Xingye; Li, Ge; Li, Matthew; Xiao, Xingcheng; Yu, Aiping; Chen, Zhongwei
Abstract: Manganese dioxide/carbon nanocomposites with partially graphitized hierarchical porous structure have been designed and synthesized. A high specific capacitance of 412 F g −1 and excellent rate capability of these composites can be achieved owing to the interconnected meso- and micro-porous structure and the graphitic pore walls facilitating the ion diffusion and electron transportation, respectively, which is highly demanded for high-performance supercapacitor electrodes materials. Even at a high scan rate of 100 mV s −1, a specific capacitance of 251 F g −1 can be obtained, corresponding to 61% capacitance retention. Moreover, a long cycling stability with initial capacitance retention of ∼88% is obtained after over 4000 cycles at a current density of 1.0 A g −1 . This work presents an efficient electrode materials design and a novel composite which holds great promise in high-performance supercapacitor applications.